2013
DOI: 10.1039/c3lc50105a
|View full text |Cite
|
Sign up to set email alerts
|

Study of endothelial cell apoptosis using fluorescence resonance energy transfer (FRET) biosensor cell line with hemodynamic microfluidic chip system

Abstract: To better understand how hyperglycemia induces endothelial cell dysfunction under the diabetic conditions, a hemodynamic microfluidic chip system was developed. The system combines a caspase-3-based fluorescence resonance energy transfer (FRET) biosensor cell line which can detect endothelial cell apoptosis in real-time, post-treatment effect and with a limited cell sample, by using a microfluidic chip which can mimic the physiological pulsatile flow profile in the blood vessel. The caspase-3-based FRET biosen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
51
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 30 publications
(40 reference statements)
0
51
0
Order By: Relevance
“…In our previous studies, we showed that fluid SS induced endothelial cell apoptosis by elevating reactive oxygen species (ROS) levels [19, 20]. To determine whether fluid SS has similar effects on CTCs, we measured the levels of ROS by pre-incubating cells with an ROS-detecting dye, CM-H 2 DCFDA (10 μM), for 30 minutes before injecting them into either zebrafish circulation or a microfluidic system.…”
Section: Resultsmentioning
confidence: 99%
“…In our previous studies, we showed that fluid SS induced endothelial cell apoptosis by elevating reactive oxygen species (ROS) levels [19, 20]. To determine whether fluid SS has similar effects on CTCs, we measured the levels of ROS by pre-incubating cells with an ROS-detecting dye, CM-H 2 DCFDA (10 μM), for 30 minutes before injecting them into either zebrafish circulation or a microfluidic system.…”
Section: Resultsmentioning
confidence: 99%
“…Among them, hemodynamic SS is the main focus of this study because it has been reported that SS generated by the bloodstream can destroy cancer cells, rendering the metastatic process ineffective212. Previously, several studies have investigated the effects of SS on endothelial cells131415, cardiovascular disease16, atherosclerosis17, etc. Recently, we also reported that physiological levels of SS could induce apoptosis in circulating breast cancer cells18.…”
mentioning
confidence: 99%
“…Caspase‐3 FRET sensor cells were applied to detect apoptosis in our previous studies (Anand et al, ; G. G. Chiew et al, ; Fu et al, ; X. F. Liu, Yu, Dalan, Liu, & Luo, ; Luo et al, ; H. Tian et al, ; Yu, Liu, Chin, Liu, & Luo, ; Zhu et al, ). In this study, we extended its utilization to drug screening by using the net YFP intensity of sensor cells to quantify cell density and proliferation.…”
Section: Resultsmentioning
confidence: 99%